miR-181a-5p mediates the effects of BMP4 on intestinal cell proliferation and differentiation - Chang Li; Yuning Zhou; Zhijie Yin; Yinping Jiang; Jinpeng Liu; Heidi L. Weiss; Qingding Wang; B. Mark Evers (Cell Death and Disease)
Abstract The intestinal mucosa undergoes a dynamic process of continual proliferation, differentiation, and apoptosis. Delineating the mechanisms involved in intestinal epithelial cell (IEC) differentiation is crucial to our understanding of not only normal gut adaptation but also aberrant intestinal growth. Bone morphogenetic protein (BMP) signaling is a pivotal regulator of intestinal proliferation and differentiation. However, the molecular underpinnings of the BMP pathway in this context are not entirely known. Here, we show a key role for the BMP4/microRNA (miR)-181/glycolysis signaling pathway in the maintenance of intestinal epithelial cell proliferation and differentiation. Treatment with BMP4 increased the expression of enterocyte markers and decreased proliferation of IECs, and importantly, decreased the expression of miR-181a-5p in mouse and human intestinal organoids. miR-181a-5p is a member of the miR-181 family with the highest expression in IECs. Treatment with locked nucleic acid (LNA) miR-181a-5p inhibitor significantly increased enterocyte differentiation as noted by increased expression of enterocyte markers in human and mouse intestinal organoids. In addition, LNA miR-181a-5p inhibitor repressed intestinal stem cell self-renewal as noted by the decreased organoid forming efficiency and expression of Ki67, cyclin D1, OLFM4 in human and mouse intestinal organoids. Moreover, in vivo administration of LNA miR-181a-5p inhibitor enhanced increased intestinal enterocyte differentiation and repressed intestinal cell proliferation. In contrast, overexpression of miR-181a-5p mimic decreased basal and BMP4-induced expression of enterocyte markers. Moreover, BMP4 treatment or inhibition of miR-181a-5p repressed hexokinase (HK) 1 expression and inhibited glycolysis. Consistently, knockdown of HK1 or inhibition of glycolysis using 2-deoxyglucose (2-DG) promoted enterocyte maturation and inhibited proliferation of IECs. Together, we provide evidence showing that miR-181a-5p inhibits intestinal enterocyte differentiation and promotes IEC proliferation through HK1-dependent glycolysis. Importantly, our findings identify miR-181a-5p as downstream in mediating BMP4 induction of enterocyte differentiation and inhibition of proliferation in IECs.